Differential changes of metabolic brain activity and interregional functional coupling in prefronto-limbic pathways during different stress conditions: functional imaging in freely behaving rodent pups - Bock, Joerg; Riedel, Anett; Braun, Katharina (Frontiers in Cellular Neuroscience, 2012)
The trumpet-tailed rat or degu (Octodon degus) is an established model to investigate the consequences of early stress on the development of emotional brain circuits and behavior. The aim of this study was to identify brain circuits, that respond to different stress conditions and to test if acute stress alters functional coupling of brain activity among prefrontal and limbic regions. Using functional imaging (2-Fluoro-deoxyglucose method) in 8-day-old male degu pups the following stress conditions were compared: (A) pups together with parents and siblings (control), (B) separation of the litter from the parents, (C) individual separation from parents and siblings, and (D) individual separation and presentation of maternal calls. Condition (B) significantly downregulated brain activity in the prefrontal cortex, hippocampus, nucleus accumbens (NAcc), and sensory areas compared to controls. Activity decrease was even more pronounced during condition (C), where, in contrast to all other regions, activity in the PAG was increased. Interestingly, brain activity in stress-associated brain regions such as the amygdala and habenula was not affected. In condition (D) maternal vocalizations “reactivated” brain activity in the cingulate and precentral medial cortex, NAcc, and striatum and in sensory areas. In contrast, reduced activity was measured in the prelimbic and infralimbic cortex (IL) and in the hippocampus and amygdala. Correlation analysis revealed complex, region- and situation-specific changes of interregional functional coupling among prefrontal and limbic brain regions during stress exposure. We show here for the first time that early life stress results in a widespread reduction of brain activity in the infant brain and changes interregional functional coupling. Moreover, maternal vocalizations can partly buffer stress-induced decrease in brain activity in some regions and evoked very different functional coupling patterns compared to the three other conditions.